MOTIVE AND CHARACTER EDUCATIONAL VALUES IN NOVEL THE INVENTION OF HUGO CABRET BY BRIAN SELZNICK - yatmi yatmi (Universitas Indraprasta PGRI, 2022)
This is a descriptive qualitative research that uses a psychological approach. The data source of this research is the novel The Invention of Hugo Cabret by Brian Selznick, publisher of Scholastic Press, New York (original version) in 2007, Mizan Fantasi (Indonesian version) in 2012. The research data are in the form of words, phrases and sentences that related with the main character's motives and the character education values in the novel. Data obtained by reading and note taking techniques. This objective of this study to analyze the existence of the main character's action motives and the value of character education in the novel The Invention of Hugo Cabret by Brian Selznick. The results of the analysis obtained the following conclusions: 1. Hugo's motives as the main character there are 20 quotes, namely as follows: a) motives for physical needs there are 3 quotations, b) motives for security and safety needs are 4 quotations, c) motives for trust and compassion consist from 5 quotations, d) the motive for self-esteem needs there are 3 quotations, e). The motives for self-actualization needs are 6 quotations. The prominent action motive is the motive for self-actualization needs. 2. The value of character education contained in Brian's novel The Invention of Hugo Cabret, consisting of; a) religious 2 quotes, b) honest 4 quotes, c) discipline 3 quotes, d) hard work 7 quotes, e) creative 2 quotes, f) independent 1 quote, g) curiosity 4 quotes, h) appreciate achievement 2 quotes, i) friends 3 quotes, j) peace love 1 quote, k) likes to read 2 quotes, l) social care 4 quotes, m) responsibility 2 quotes.